The Role of Brand Image in Mediating the Influence of Brand Ambassador and Electronic Word of Mouth on Purchase Intention on Product Scarlett Whitening - Al-Fatwa, Anissa; Siagian, Dergibson; Dema, Yosef (Jurnal Manajemen, 2024)
In the era of globalization and modernization, the growth of internet users in Indonesia reflects significant changes in people's lifestyles, including their beauty and skin care needs. Skincare has become an essential part of the beauty routine, heavily influenced by societal perceptions of beauty. This research focuses on Scarlett Whitening, a local beauty brand, which experienced a decline in sales starting in July 2023. The method used in this research is a causal method with structural equation modeling (SEM). This study aims to investigate the impact of electronic word-of-mouth (e-WOM) and brand ambassadors on purchase intentions. The results show that while brand ambassadors do not significantly influence purchase intention, e-WOM does. Furthermore, brand image acts as a mediator between e-WOM and purchase intention, but does not mediate the influence of brand ambassadors.